The U-shaped association between normal-range serum bile acid levels and prognosis of Coronary Heart Disease - Xu, Yu; Ding, Ning; Hua, Rui; Wu, Yue; Li, Ting; Yuan, Zuyi (Frontiers in Endocrinology, 2026)
BackgroundPrevious studies have shown that serum total bile acid levels are associated with both the presence of Coronary Heart Disease and the severity of coronary artery lesions. Coronary Heart Disease progression frequently involves an imbalance in bile acid metabolism. This study aims to evaluate the predictive value of total bile acid levels for the occurrence of major adverse cardiovascular events in patients with Coronary Heart Disease.MethodA total of 2,974 patients with Coronary Heart Disease who met the inclusion criteria were categorized into four groups based on the quartiles of their total bile acid levels: Group 1 (0.2-1.9 µmol/L, n = 760), Group 2 (1.9-3.1 µmol/L, n = 758), Group 3 (3.1-5.1 µmol/L, n = 741), and Group 4 (5.1-10 µmol/L, n = 715). Survival differences among the groups were evaluated using Kaplan-Meier curves. Multivariate Cox regression analysis was performed to assessed their associations. Restricted cubic spline models were employed to investigate potential nonlinear relationships. Subgroup interaction and incremental predictive value analyses were additionally performed.ResultsOver a median follow-up period of 75 months, Group 2 exhibited a significantly lower incidence of major adverse cardiovascular events compared to the other groups. Kaplan-Meier survival analyses also demonstrated that participants in Group 2 exhibited significantly higher cumulative survival rates free of major adverse cardiovascular events compared to those in the other groups. Multivariate Cox regression revealed that both higher and lower total bile acid levels were associated with an increased risk of major adverse cardiovascular events (HRQ1 = 1.91, p<0.001; HRQ4 = 1.62, p<0.001). Furthermore, Restricted cubic spline analysis indicated a significant nonlinear, U-shaped relationship between total bile acid levels and major adverse cardiovascular events, which was statistically significant in males but not in females. Moreover, risk model analysis demonstrated that adding TBA to a conventional model significantly improved risk discrimination and reclassification.ConclusionTotal bile acid levels have predictive value for major adverse cardiovascular events in Coronary Heart Disease patients. This finding substantiates the predictive value of total bile acid as an effective risk stratification tool for patients with Coronary Heart Disease after hospital discharge.